Evaluation of yield and agronomic components of three-way cross maize hybrids under low-light environment. Issue 1 (April 2020) - Andayani, NN; Riadi, M; Rafiuddin; Kalqutny, S H; Efendi, R; Azrai, M
Abstract: The development and the use of low light tolerant varieties is one of the technologies to overcome the limitations of hybrid maize in the land with the low-light condition. The objectives of the study were to determine the effect of shading/low light intensity on the growth and production of three-way cross maize hybrid, as well to generate hybrid variety that is tolerant to the shade stress condition. The research was conducted under two different environmental conditions, i.e. Screen House environment with 35% of paranet shading condition, and normal environment condition at Indonesian Cereals Research Institute experimental station from July to October 2018. The research was arranged in a Randomized Block Design (RBD) with three replications. The research material consisted of nine three-way crosses (STJ01-STJ09) and two check varieties (Bima-19 and P35). The results indicated that as many as four genotypes performed high yield under 35% shading condition i.e. STJ01, STJ02, STJ06 and STJ07 which yielded 5.60; 6.55; 5.87 and 6.15 t/ha respectively. Correlation analysis indicated various traits have a direct effect on grain yield i.e. ear weight, kernel net weight, ear length, number of kernels per row and kernel weight per ear. As for shading condition, the positive correlations were found for ear weight, ear length, number of kernels per row and kernel weight per ear characters.